Financial Performance Analysis using the Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) Method - Cariniah Cariniah; Lasminiasih Lasminiasih (Green Publisher Indonesia, 2022)
The Indonesian economy at this time cannot be separated from financial services such as banking. Banks on a daily basis need to show their performance so that bank service users can see whether the bank is good or not. The purpose of this study was to compare the soundness of banks at PT Bank Capital Indonesia Tbk and PT Bank Jago Tbk for the 2018-2020 period using the RGEC method. The object of this research is PT Bank Capital Indonesia Tbk and PT Bank Jago Tbk. The data used is quantitative data. The data source used is secondary data in the form of financial reports that have been published by the official website www.bankcapital.co.id and www.jago.com or through the official website www.idx.co.id. The technique used is the documentation technique. And the analysis technique used is Bank Indonesia regulation No. 13/1/PBI/2011. The results of this study indicate that the assessment of the Risk Profile on the NPL ratio of PT Bank Capital Indonesia Tbk and PT Bank Jago Tbk in Healthy conditions, and the assessment of the LDR ratio of PT Bank Capital Indonesia Tbk in Very Healthy conditions while PT Bank Jago Tbk in Healthy conditions. For the assessment of GCG aspects, the Self Assessment of PT Bank Capital Indonesia Tbk is in Good Enough condition, while PT Bank Jago Tbk is in Good condition. Furthermore, for the assessment of the Earnings aspect of the ROA ratio to PT Bank Capital Indonesia Tbk in an Unhealthy condition, while PT Bank Jago Tbk in an Unhealthy condition. And the assessment of the Capital aspect on the CAR ratio of PT Bank Capital Indonesia Tbk and PT Bank Jago Tbk in Very Healthy condition.